Pengaruh Dewan Komisaris Independen, Komite Audit Independen, dan Kepemilikan Institusional Non-Pemerintah terhadap Potensi Financial Statement Fraud pada BUMN Non-Keuangan Terdaftar di BEI - Gabriella Ratna Mawarni; Pigo Nauli (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study examines the effect of an independent board of commissioners, an independent audit committee, and non-government institutional ownership on the potential for financial statement fraud in non-financial State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during 2020–2024. Unlike previous studies that generally use binary variables and focus on private firms, this research employs the Beneish M-Score as a continuous measure to detect fraud potential. It also distinguishes non-government institutional ownership from government ownership to represent a more independent external monitoring mechanism. The study analyzed 22 non-financial SOEs, generating 110 observations over a five-year period. Hypotheses were tested using panel data regression with the Common Effect Model (CEM). The results show that all independent variables simultaneously have a significant effect on the potential for financial statement fraud (F = 7.971; p < 0.01). Partially, the independent board of commissioners has a significant positive effect on fraud potential (β = 0.015; p = 0.030), indicating the possibility of symbolic governance practices. The independent audit committee does not significantly influence fraud potential (p = 0.087). Meanwhile, non-government institutional ownership has a significant negative effect (β = −0.013; p = 0.044), demonstrating its effectiveness as an external monitoring mechanism. These findings suggest that formal compliance with corporate governance regulations alone is insufficient to reduce fraud risk and highlight the importance of ownership diversification as an anti-fraud strategy in SOEs.